1990
DOI: 10.1038/bjc.1990.100
|View full text |Cite
|
Sign up to set email alerts
|

Milk consumption and cancer incidence: a Norwegian prospective study

Abstract: Summary Relationships between milk intake and cancer incidence were investigated after I 1I years of follow-up of 15,914 individuals. A diagnosis of cancer was made in a total of 1,422 individuals. No association was established with total cancer incidence, in analyses adjusted for sex, age and residential characteristics. However, a strong positive association with milk consumption was observed for cancers of the lymphatic organs (odds ratio 3.4 for > 2 glasses per day vs <1; 95% confidence interval 1. 4-8.2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
3
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 25 publications
4
69
3
3
Order By: Relevance
“…11 The results of our study were in accordance with results from previous studies, except that milk consumption had an association with deaths from hematopoietic neoplasm excluding lymphoma.…”
Section: Type Lymphomasupporting
confidence: 83%
See 2 more Smart Citations
“…11 The results of our study were in accordance with results from previous studies, except that milk consumption had an association with deaths from hematopoietic neoplasm excluding lymphoma.…”
Section: Type Lymphomasupporting
confidence: 83%
“…One cohort study has demonstrated a positive association between milk consumption and death from lymphoma, 11 but not with death from leukemia or multiple myeloma. In contrast, the other study did not find any significant relationship between milk consumption and morbidity of lymphoma or leukemia.…”
Section: Type Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Chiu et al 403 found no association with the highest versus the lowest category of dairy intake (RR 5 1.04, 95% CI: 0.61-1.77). Associations with milk consumption have varied; some studies have reported positive associations, 402,405,406,409,413 whereas others have reported inverse or no associations. 370,373,403,405 Findings on fruit consumption have been inconsistent with some studies reporting an inverse association with risk of NHL, 368,385,403,405,407,414 but other studies have not reported such associations.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Milk is the dairy product that shows the most consistent relationship with CRC risk. Of the cohort studies to date that have investigated this relationship, most showed nonsignificant decreased risks of CRC with increasing milk intake (12,17,19,22,23,27,29,30,33,34,38) . Most studies have considered all types of milk together, but where these have been separated there are differences between low-fat v. whole milk.…”
Section: Epidemiological Studies Of Dairy Products and Colorectal Canmentioning
confidence: 99%